Can fuzzy extension of Delphi-analytical hierarchy process improve hospital site selection?. (1st January 2014) - Chatterjee, Debmallya
Applications of Analytical Hierarchy Process (AHP) and its Fuzzy Extension (FAHP) can be witnessed in different Multi-criteria Decision- Making (MCDM) situations including location selection. However, the use of such a prominent MCDM tool is limited when it comes to hospital site selection in India. This paper makes an attempt to do a formal study of hospital site selection in India using AHP and its fuzzy extension. The study embeds Delphi both with AHP and FAHP in generating consensus and does a comparative analysis to verify the supremacy of one over another. Three rural locations from India are considered for a potential hospital in the study. Results indicate 'cost of land' as the most important sub-factor across both the integrated models followed by 'population characteristics'. D-AHP and D-FAHP has resulted in varying weights for few sub-factors nevertheless the differences are not statistically significant.